2006
DOI: 10.1007/s00586-006-0264-z
|View full text |Cite
|
Sign up to set email alerts
|

Do MRI findings correlate with mobility tests? An explorative analysis of the test validity with regard to structure

Abstract: To find out whether segmental magnetic resonance imaging (MRI) findings such as intervertebral disc degeneration (DD) and facet joint osteoarthritis (FJO) are associated with motion deficiencies as seen in common mobility tests and observed range of motion (ROM). A total of 112 female subjects, nurses and office workers, with and without low back pain, were examined by clinical experts, and lumbar mobility was measured including modified Schober, fingertip-to-floor distance (FTFD) and ZEBRIS motion analysis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 48 publications
1
12
1
1
Order By: Relevance
“…The use of kMRI may be helpful in these situations in determining spinal stability. [25][26][27][28][29] Combined with digital imaging software that allows for accurate and precise quantifi cation of spinal motion, kMRIs could potentially help spine surgeons create more complete clinical assessments of their patients in some situations. 30 , 31 Previous reports have shown that disc degeneration is strongly associated with changes in segmental motion.…”
Section: Discussionmentioning
confidence: 99%
“…The use of kMRI may be helpful in these situations in determining spinal stability. [25][26][27][28][29] Combined with digital imaging software that allows for accurate and precise quantifi cation of spinal motion, kMRIs could potentially help spine surgeons create more complete clinical assessments of their patients in some situations. 30 , 31 Previous reports have shown that disc degeneration is strongly associated with changes in segmental motion.…”
Section: Discussionmentioning
confidence: 99%
“…C adaver specimens, 19 various imaging techniques, 17,20,24 and in vivo surgically inserted pins 4,6,21,23 have all been used to understand the complexities of segmental spinal motion. Each method has contributed to our understanding of the motion that occurs at the spine.…”
Section: Discussionmentioning
confidence: 99%
“…The onset, history of symptoms, and mechanism of injury typically varies. Physical examination is essential, but evidence suggests [12‐17] that reliability for definitive structural involvement is lacking. Furthermore, many of the provocative physical examination maneuvers that are used to identify potential pain sources, such as the sacroiliac joint and/or hip joint, overlap and are difficult to truly isolate.…”
Section: Discussionmentioning
confidence: 99%